2011
DOI: 10.1097/ico.0b013e3182096789
|View full text |Cite
|
Sign up to set email alerts
|

Keratopathy After Cross-linking for Keratoconus

Abstract: Cross-linking associated with sterile keratitis is an unusual entity of unknown etiology, which can lead to stromal scarring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 20 publications
0
12
0
2
Order By: Relevance
“…Raiskup-Wolf et al 17 found a failure rate of 14% at 12 months, defined as progression of K-max by at least 0.5 D. Wittig-Silva et al 3 had a smaller failure rate of 2.4%, but this was defined as progression by 2 D at 36 months. 3,21,29,30 However, serious microbial keratitis can develop with a range of pathogens, such as Pseudomonas, Escherichia Coli, Staphylococcus aureus, Acanthamoeba, and Fusarium species, having been implicated. To put the failure rates into perspective, we must bear in mind the natural progression history of keratoconus.…”
Section: Safety Conventional Low-fluence Collagen Cross-linkingmentioning
confidence: 99%
“…Raiskup-Wolf et al 17 found a failure rate of 14% at 12 months, defined as progression of K-max by at least 0.5 D. Wittig-Silva et al 3 had a smaller failure rate of 2.4%, but this was defined as progression by 2 D at 36 months. 3,21,29,30 However, serious microbial keratitis can develop with a range of pathogens, such as Pseudomonas, Escherichia Coli, Staphylococcus aureus, Acanthamoeba, and Fusarium species, having been implicated. To put the failure rates into perspective, we must bear in mind the natural progression history of keratoconus.…”
Section: Safety Conventional Low-fluence Collagen Cross-linkingmentioning
confidence: 99%
“…One of the most common complications appears to be the development of sterile corneal infiltrates (Figure ). These have been seen in up to 7.6 per cent of cases and resolve with an increase in topical steroid therapy but sometimes leaving a residual scar .…”
Section: Adverse Effects and Safetymentioning
confidence: 99%
“…With a rapidly increasing number of cross-linking procedures being performed around the world, there is an increasing number of reports 29,32,34,36,45,[70][71][72][73][74][75][76][77][78][79][80][81][82][83] of adverse events, which are outlined in Table 2. While a minor degree of stromal oedema seen on slitlamp examination may be seen in up to 70 per cent of patients in the first month and a temporary haze in 9.8 per cent 32 (Figure 4), more significant stromal haze has been reported in up to 8.6 per cent of treated eyes and may persist for up to six months.…”
Section: Adverse Effects and Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, 2 cases of keratopathy have been reported after uneventful CXL for grade 3 keratoconus [122]. The pathogenesis in these cases remained unidentified.…”
Section: Complications After CXLmentioning
confidence: 99%